Effect of Sevoflurane and Isoflurane Anaesthesia on Cognitive Function in Early Postoperative Period (Annals of Medical Research, 2021)
None
Keywords: Anaesthesia, Cognitive function, Recovery, Sevoflurane, İsoflurane